A Mastication Mechanism Designed for Testing Temporomandibular Joint Implants - Ryan J. Frayne; Marvin Schwartz; James P. Dickey (Applied Bionics and Biomechanics)
The development of temporomandibular joint implants has involved simplified mechanical tests that apply pure vertical forces or pure rotational movements to the implant. The aim of this study was to develop a biological based mastication mechanism and conduct preliminary testing of a novel temporomandibular joint implant. The mechanism was designed to mimic temporomandibular joint loads by performing compression and anterior/posterior translation. Pilot testing was performed on six implant/joint specimens for seven consecutive hours, completing approximately 22,000 cycles at a frequency of approximately 1 Hz. Each cycle had a joint compression phase (67.3 N over 0.15 s) followed by a translation phase (8.67 N over 0.43 s) that was similar to joint loads/motions that have been reported in vivo. This new mastication mechanism incorporates both anatomical and mechanical variability. The use of biological specimens is an important approach that can help bridge the gap between traditional synthetic implant materials/mechanical testing and in vivo testing.